Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/adma.201304370
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Recycling Solution for Polystyrene Achieved by the Synthesis of Renewable Poly(thioether) Networks Derived from d‐Limonene

Abstract: Nanocomposite polymers have been prepared using a new sustainable materials synthesis process in which d-Limonene functions simultaneously both as a solvent for recycling polystyrene (PS) waste and as a monomer that undergoes UV-catalyzed thiol-ene polymerization reactions with polythiol co-monomers to afford polymeric products comprised of precipitated PS phases dispersed throughout elastomeric poly(thioether) networks. These blended networks exhibit mechanical properties that greatly exceed those of either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Polymer Synthesis, Micromolding and Mechanical Characterization : To synthesize PLT32o prepolymer, a one‐pot synthesis was carried out using a D‐limonene‐capped TMPTMP macromonomer similar to the M1 Macromonomer reported in Scheme 4 by Claudino et al and the co‐monomer 1,10 DDT. To create a photoreactor, a UVP CL‐1000 cross‐linking chamber with 365 nm bulbs was positioned on top of a magnetic stir plate in which UV irradiation of monomers could be carried out under vigorous stirring conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer Synthesis, Micromolding and Mechanical Characterization : To synthesize PLT32o prepolymer, a one‐pot synthesis was carried out using a D‐limonene‐capped TMPTMP macromonomer similar to the M1 Macromonomer reported in Scheme 4 by Claudino et al and the co‐monomer 1,10 DDT. To create a photoreactor, a UVP CL‐1000 cross‐linking chamber with 365 nm bulbs was positioned on top of a magnetic stir plate in which UV irradiation of monomers could be carried out under vigorous stirring conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Hubbell and co‐workers first described photopolymerizable degradable thiol‐acrylate systems, and Anseth and co‐workers custom synthesized and functionalized thiol‐acrylates to control degradation rate and cell‐material interactions . Hearon et al demonstrated a one‐pot synthesis of a thiol‐ene polymer wherein brief heating and/or UV irradiation of a mixture of trimethylolpropane tris(3‐mercaptopropionate) (TMPTMP) and the naturally occurring citrus‐derived extract D‐limonene afforded a homogenous solution that could be transferred to a mold without further polymer network formation occurring until subsequent exposure to UV irradiation. Synthetic, processing and environmental health and safety advantages of PLT32o make this material an attractive candidate for biomedical engineering applications where recapitulation of the niche of the target cells through fabrication of complex templates with patterned 3D pore microstructures is desired.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is common to many low transition temperature poly(thiother) networks which are elastomeric and possess poor mechanical integrity at and above 25 °C . Works are underway to involve high glass transition resins, such as polystyrene, or poly(methyl methacrylate for example, to increase modulus and improve the toughness and mechanical stress of the films …”
Section: Resultsmentioning
confidence: 99%
“…Limonene was reacted with polythiol co‐monomers through a UV‐catalyzed thiol–ene polyaddition reaction to give nanocomposite materials in which precipitated polystyrene phases were dispersed through elastomeric poly(thioether) networks . Interestingly, limonene was simultaneously utilized as both a monomer and as a solvent for recycling polystyrene waste in this reaction, and the mechanical properties of these materials greatly surpassed those of poly(thioether) network homopolymers and polystyrene alone.…”
Section: Thiol–ene Reaction For the Synthesis Of Terpene‐based Monomementioning
confidence: 99%